A Short-Term Follow-up Study on Hormonal Changes after Three to Six Months of SARS-CoV-2 Infection - Arafat, Shohael Mahmud; Banu, Hurjahan; Morshed, Md Shahed; Sultana, Nusrat; Hasanat, Muhammad Abul (Bangladesh Journal of Medicine, 2025)
Background: Long-COVID symptoms may develop following coronavirus disease 2019 (COVID-19) and mimic various endocrine dysfunctions. Hormonal assessment during and after COVID may be necessary to distinguish between these conditions. This study evaluated hormone status during active infection and after three to six months post-COVID-19 infection. Methods: This prospective study initially included ninety-one noncritically ill hospitalized patients with COVID-19 infection (18-65 years, m/f: 37/54). The participants were reassessed three to six months after their hospitalization.Eight patients died during their hospital stay, and we were able to collect follow-up data for only fifteen [age (years): 47.3±13.3, m/f: 6/9] out of eighty-three survived patients. Thyroid (TSH, FT4, and FT3), adrenal (basal cortisol and ACTH), and sex-steroid (total testosterone and dehydroepiandrosterone sulfate) axes were evaluated and compared with laboratory cut-offs at diagnosis and three to six months later. All the hormones were measured by chemiluminescent microparticle immunoassay. Results: At baseline, six participants (40.0%) had normal values for all the studied hormones, five (33.3%) exhibited one abnormality, and four (26.7%) displayed two abnormalities. After three months of COVID-19 infection, four had normal values (26.7%), six (40.0%) had one abnormality, three (20.0%) had two, and two (13.3%) had three abnormalities in the studied hormone status. Conclusion: Endocrine dysfunctions are not uncommon during short-term follow-up after COVID-19, and hormonal evaluations may be necessary, particularly for symptomatic patients. Bangladesh J Medicine 2025; 36(3): 136-141